Acquisition of old Romanian periodicals in the rare documents collection (Confluenţe Bibliologice, 2024)
The article provides information on the acquisition process of serial publications for the Rare Documents Collection, focusing on publications with scientific, historical, and cultural profiles. It emphasizes the importance of these primary sources of information for highlighting the research achievements of the Romanian people. The serial publications encompass a wide range of articles and will serve as valuable resources for study and research at the USARB Scientific Library.
Keywords: periodicals; Rare Book Collection